Nudge, nudge, wink, wink: Nudging is giving reasons - Levy, Neil (Ergo (Ann Arbor), 2019)
Nudges are, roughly, ways of tweaking the context in which agents choose in order to bring them to make choices that are in their own interests. Nudges are controversial: opponents argue that because they bypass our reasoning processes, they threaten our autonomy. Proponents respond that nudging, and therefore this bypassing, is inevitable and pervasive: if we do not nudge ourselves in our own interests, the same bypassing processes will tend to work to our detriment. In this paper, I argue that we should reject the premise common to opponents and proponents: that nudging bypasses our reasoning processes. Rather, well designed nudges present reasons to mechanisms designed to respond to reasons of just that kind. In this light, it is refusing to nudge that threatens our autonomy, by refusing to give us good reasons for action.